Single-Cell Analysis of Circulating Tumor Cells - Thiele, Jana- A; Pitule, Pavel; Hicks, James; Kuhn, Peter (Methods in molecular biology, 2019)
Circulating tumor cells (CTCs) are rare cells that can be found in the peripheral blood of cancer patients. They have been demonstrated to be useful prognostic markers in many cancer types. Within the last decade various methods have been developed to detect rare cells within a liquid biopsy from a cancer patient. These methods have revealed the phenotypic diversity of CTCs and how they can represent the complement of cells that are found in a tumor. Single-cell proteogenomics has emerged as an all-encompassing next-generation technological approach for CTC research. This allows for the deconstruction of cellular heterogeneity, dynamics of metastatic initiation and progression, and response or resistance to therapeutics in the clinical settings. We take advantage of this opportunity to investigate CTC heterogeneity and understand their full potential in precision medicine.The high-definition single-cell analysis (HD-SCA) workflow combines detection of the entire population of CTCs and rare cancer related cells with single-cell genomic analysis and may therefore provide insight into their subpopulations based on molecular as well as morphological data. In this chapter we describe in detail the protocols from isolation of a candidate cell from a microscopy slide, through whole-genome amplification and library preparation, to CNV analysis of identified cells from the HD-SCA workflow. This process may also be applicable to any platform starting with a standard microscopy slide or isolated cell of interest.
Keywords: mutace; DNA Copy Number Variations; Neoplasms; nádory; individualizovaná medicína; Proteogenomics; variabilita počtu kopií segmentů DNA; proteogenomika; analýza jednotlivých buněk; lidé; nádorové cirkulující buňky; Precision Medicine; Single-Cell Analysis; Neoplastic Cells, Circulating; Mutation; Humans